A Framework for Coordination between Obstetric and Pediatric Providers in Public Health Emergencies: Lessons Learned from the Zika Outbreak in the United States, 2015 to 2017 - Leeb, Rebecca T.; Cree, Robyn A.; Aird, Laura; DeBiasi, Roberta L.; Driggers, Rita W.; Garbarczyk, Elizabeth; Mofenson, Lynne M.; Needle, Scott; Rodriguez, Jeannie; Curry, Christine; García, Francisco; Godfred-Cato, Shana; Hawks, Debra; Rosenblum, Elizabeth; Dziuban, Eric; Hudak, Mark (American Journal of Perinatology, 2020)
Emergency response to emerging threats with the potential for vertical transmission, such as the 2015 to 2017 response to Zika virus, presents unique clinical challenges that underscore the need for better communication and care coordination between obstetric and pediatric providers to promote optimal health for women and infants. Published guidelines for routine maternal-infant care during the perinatal period, and models for transitions of care in various health care settings are available, but no broad framework has addressed coordinated multidisciplinary care of the maternal-infant dyad during emergency response. We present a novel framework and strategies to improve care coordination and communication during an emergency response. The proposed framework includes (1) identification and collection of critical information to inform care, (2) key health care touchpoints for the maternal-infant dyad, and (3) primary pathways of communication and modes of transfer across touchpoints, as well as practical strategies. This framework and associated strategies can be modified to address the care coordination needs of pregnant women and their infants with possible exposure to other emerging infectious and noninfectious congenital threats that may require long-term, multidisciplinary management.Key Points
Keywords: maternal and infant health; care coordination; communication; congenital threat; public health